T-tubule disorganization and defective excitation-contraction coupling in muscle fibers lacking myotubularin lipid phosphatase - Al-Qusairi, L.; Weiss, N.; Toussaint, A.; Berbey, C.; Messaddeq, N.; Kretz, C.; Sanoudou, D.; Beggs, A. H.; Allard, B.; Mandel, J. L.; Laporte, J.; Jacquemond, V.; et al. (Proc Natl Acad Sci U S AProc Natl Acad Sci U S AProc Natl Acad Sci U S A, 2009)
Skeletal muscle contraction is triggered by the excitation-contraction (E-C) coupling machinery residing at the triad, a membrane structure formed by the juxtaposition of T-tubules and sarcoplasmic reticulum (SR) cisternae. The formation and maintenance of this structure is key for muscle function but is not well characterized. We have investigated the mechanisms leading to X-linked myotubular myopathy (XLMTM), a severe congenital disorder due to loss of function mutations in the MTM1 gene, encoding myotubularin, a phosphoinositide phosphatase thought to have a role in plasma membrane homeostasis and endocytosis. Using a mouse model of the disease, we report that Mtm1-deficient muscle fibers have a decreased number of triads and abnormal longitudinally oriented T-tubules. In addition, SR Ca(2+) release elicited by voltage-clamp depolarizations is strongly depressed in myotubularin-deficient muscle fibers, with myoplasmic Ca(2+) removal and SR Ca(2+) content essentially unaffected. At the molecular level, Mtm1-deficient myofibers exhibit a 3-fold reduction in type 1 ryanodine receptor (RyR1) protein level. These data reveal a critical role of myotubularin in the proper organization and function of the E-C coupling machinery and strongly suggest that defective RyR1-mediated SR Ca(2+) release is responsible for the failure of muscle function in myotubular myopathy.
Keywords: *Lipid Metabolism; Animals; Calcium Channels/metabolism; Calcium/metabolism; Gene Expression Regulation; Homeostasis/genetics; Ion Channel Gating; Mice; Mice, Knockout; Muscle Contraction/*physiology; Muscle Fibers, Skeletal/*enzymology/*pathology/ultrastructure; Protein Tyrosine Phosphatases, Non-Receptor/*deficiency/metabolism; Sarcoplasmic Reticulum/*enzymology/*pathology/ultrastructure